Territorial relations in the South China Sea in the international legal doctrine of the Peopleʼs Republic of China - BILOTSKY, Сергій (Ius Modernum, 2023)
The development of international maritime law, the relevant activities of international judicial institutions, as well as their compliance with specific national legal doctrines require their legal analysis. One of the last important international court decisions in the field of maritime law was the decision of the Permanent Chamber of the Arbitration Court in The Hague in case No. 2013-19 of July 12, 2016 regarding the dispute between the Philippines and the PRC regarding the non-recognition of the so-called Chinese "nine-dash line", and the corresponding illegal construction of artificial structures. At the same time, the Peopleʼs Republic of China did not recognize the decision of the Permanent Chamber, and Chinese scholars were building appropriate legal justifications for this position. The situation is similar to the Russian Federationʼs non-recognition of the decision of the same judicial body regarding the nationalization of the property of Ukrainian Naftogaz in Crimea and, accordingly, requires investigation. The article uses the comparative legal method, the method of legal analysis, and the historical method. For Chinese international lawyers, the problem of substantiating the territorial interests of the PRC in the waters of the South China Sea from the point of view of international law, together with the implementation of the "Maritime Silk Road" and "Polar Silk Road" initiatives, is an overriding priority of state importance. At the same time, the Permanent Chamber in The Hague rejected a number of inadequately substantiated arguments of the PRC, such as the existence of its "historical rights", historical waters, the legality of the "nine-dash line", the right to unilaterally issue permits for the construction of artificial islands, structures, geological works within disputed maritime spaces.